A versatile catalyst in situ self-cleaning method for excellent cycling and operational stability in small-molecule electrooxidation - Zhi-Xiang Yuan; Yingjie Gao; Shan-Qing Li; Jie Xuan; Xin-Yu Sheng; Fei Zhang; Yao Zheng; Ping Chen (eScience)
The electrochemical oxidation of small molecules is a promising approach in chemical synthesis, but catalyst deactivation due to the accumulation of poorly soluble products on the surface remains a significant challenge. To address this, we propose an in situ cleaning method using an additional oxygen evolution reaction (OER) to regenerate degraded catalysts. The OER facilitates the removal of insoluble products, thereby restoring active sites. Taking the electrochemical oxidation of tetrahydroisoquinoline (THIQ) to dihydroisoquinoline (DHIQ) as an example, we develop a highly active γ-Ni(Co)OOH anode. The OER generates oxygen, promoting the oxidation of DHIQ to IQ, which is more soluble, thus effectively removing DHIQ from the catalyst surface. After 120 cycles in a small-scale pilot test, the current stability exceeds 98%, and the product selectivity reaches 95%. This method demonstrates the highest stability to date, outperforming previous catalysts 15-fold, and can be applied to other electrocatalytic systems facing similar deactivation issues.